Limitation of solutions of some simultaneous differential equations with a retarded argument - Avdjan, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. С. Авджян. Ограниченность решении некоторых систем дифференциальных уравнений с запаздывающим аргументомA. Avdžianas. Kai kurių diferencialinių lygčių sistemų su vėluojančiu argumentu sprendinių aprėžtumas